Pengetahuan Wajib Pajak Sebagai Variabel Mediasi Hubungan Antara Sosialisasi PMK N0. 44 Tahun 2020, Kemudahan Memanfaatkan Insentif Pajak Dan Kesadaran Wajib Pajak Terhadap Kepatuhan - Siti Khairani (LPPM Universitas Multi Data Palembang, 2021)
The purpose of this study was to test whether the knowledge variable could mediate the relationship between the PMK No. socialization variables. 44 of 2020, the ease of taking advantage of tax incentives, and awareness of taxpayer compliance. The technique of collecting data is through distributing questionnaires to UMKM in KPP Ilir Timur Palembang. The analysis technique uses path analysis with the help of the SPSS program. From the result of the path analysis, there is an indirect effect of the Socialization variable (X1) on the compliance variable (Y) through the Mediation Variable (Knowledge) of 0.144 (14.4%). The convenience variable through the knowledge variable does not have a significant effect on the compliance variable. Indirectly, the awareness variable through the knowledge variable has a significant effect on the compliance variable.